Crossing the Line: Rape-Murder and the Death Penalty - Crocker, Phyllis L (2000)
When a woman is raped and then murdered, it is among the most horrifying of crimes. It is also, often, among the most sensational, notorious, and galvanizing of cases. In 1964, Kitty Genovese was raped and murdered in Queens, New York. Her murder sparked soul-searching across the country because her neighbors heard her cries for help and did not respond: it made us question whether we had become an uncaring people. During the 1970s and 80s a number of serial killers raped and murdered their victims: including Ted Bundy in Florida and William George Bonin, the “Freeway Killer,” in Southern California. In the 1990s, the sexual assault-murder of seven-year-old Megan Kanka in New Jersey contributed to a firestorm of states passing sex offender notification statutes.Rolando Cruz was released from Illinois death row in 1995, after serving eleven years for a crime he did not commit: the rape and murder of ten-year-old Jeanine Nicarico. The crime itself sent shock waves through the Chicago metropolitan area and pressure to quickly solve it contributed to Cruz's arrest and conviction. In each instance the rape-murder terrified us and made us want to impose the severest of punishments.This essay explores the validity of that conclusion by examining rape-murder as a category of death penalty cases, and by comparing the treatment of rape when it is the only crime to its treatment when it is the underlying felony in a felony-murder death penalty case